China's Competitive Performance: A Threat to East Asian Manufactured Exports? - Lall, S; Albaladejo, M (QEH (University of Oxford), 2003)
We examine China's competitive threat to East Asian neighbors in the 1990s, benchmarking performance by technology and market. Market share losses are mainly in low-technology products; Japan is the most vulnerable market. China and its neighbors are raising high-technology exports in tandem: international production systems here are leading to complementarity rather than confrontation. In direct trade with its neighbors, China is acting as an engine of export growth, with imports outpacing exports. This may change, however, as China climbs the value chain and takes over activities that have driven East Asian export growth even within integrated production systems.